Comparación del rendimiento de pinos en la reforestación de sitios marginales en Nuevo León - Domínguez Calleros, Pedro Antonio; Návar Cháidez, José de Jesús; Loera Ortíz, José Antonio (Instituto de Ecología, A.C., 2016)
The objetive this research was to evaluate plant adaptation and growth and yield of three native pine species (P. pseudostrobus Lindl., P. greggii Engelm. and P. cembroides Zucc.) as well as two exotic pine species (P. halepensis Mill. and P. brutia Ten.) planted to restore degraded lands by agricultural and grazing practices in the Sierra Madre Oriental, in Iturbide, N.L. Mexico. The adaptation and growth and yield parameters evaluated were: survival, height, diameter, stem volume and cover. These paramaters were evaluated nine years after being planted in degraded lands. P. cembroides and P. greggii had the highest rate of survival (48%) and P. brutia had the smallest survival rate (12%). P. greggii and P. cembroides showed the best and worst height growth with 5.17 and 1.16 m, respectively. P. pseudostrobus and P. greggii had as an average 10.3 cm of basal diameter while P. cembroides had only 2.38 cm. The greatest volume was showed by the species P. greggii with 29.33 m3/ha and the smallest one by the species P. cembroides with 0.342 m3/ha. To rehabilitate degraded lands in northeaster Mexico, P. greggii, P. halepensis y P. cembroides are the species recommended because of its best adaptation and growth parameters. It is recomend also, to observe the main sources of variation which control mortality of these pine species to utilize them in shorter rotations for other purposes in degraded lands of northeastern Mexico.